Kardiochirurgia dorosłychInfluence of external Dacron stent on disease progression in saphenous vein grafts - Krejca, Michał; Bochenek-Klimczyk, Krystyna; Szmagała, Przemysław; Węglarz, Przemysław; Guzy, Michał; Bolkowski, Maciej; Ulczok, Rafał; Bis, Jarosław; Skarysz, Janusz; Plewka, Andrzej; Plewka, Danuta; Nowaczyk, Grażyna; et al. (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2006)
Background: Neointimal thickening plays a critical role in vein graft disease. Aim: To construct an artificial mesh which may serve as an external stent and may be implanted during cardiac surgery, to examine the effects of the originally developed Dacron external stent on the progression of vein graft disease in an animal model and introduce into clinical practice a new outside stent. Material and methods: Samples of tissues from 21 sheep were taken for histopathology and immunocytochemistry examination 5, 9 days and 4, 6, 8, 10, and 12 weeks after implantation. In patients who underwent CABG, IVUS examination was performed after 3 and 12 months. Results and conclusions: The study showed that in venous grafts covered by an external stent, neointimal hyperplasia (NIH), infiltration with inflammatory cells and cellular proliferation in the vein wall progress slower, VEGF and flt-1 activity are modified, and endothelium formation progresses faster than in standard vein grafts. Clinical practice revealed that external stents decrease vein graft disease during the first few months post operation.